Predicting anti‑cancer drugs’ dissolution in supercritical carbon dioxide - Winslet, Billey; Paxton, Victor; Rose, Alexandrea; East, Tricia (Technium BioChemMed, 2023)
There are many different kinds of chemotherapy or chemo drugs are used for treating cancer. All of These medicine from chemical composition, how they are prescribed and given, how useful they are in treating certain types of cancer, and the side effects they might have. Nobody can deny that all medicines to treat cancer work in the different ways. The solubility of Azathioprine, as an immunosuppressive and anti-cancer drug, in supercritical carbon dioxide (SC-CO2) was measured for the first time. Under the applied conditions in terms of pressure (120–270 bar) and temperature (308–338 K), mole fractions were obtained in the range of 0.27 × 10−5 to 1.83 × 10−5. Three types of methods including (1) two equations of states (EoSs), namely Peng-Robinson (PR) and Soave–Redlich–Kwong (SRK) with vdW2 mixing rule (2) expanded liquid theory (3) nine semi-empirical density-based models were selected to correlate the solubility data of drug. Our developed correlation presents the absolute average relative deviation (AARD) of 9.54% for predicting 316 experimental measurements. After all we show that, the most accurate correlation in the literature presents the AARD = 14.90% over the same database. Furthermore, 56.2% accuracy improvement in the solubility prediction of the anti‑cancer drugs in supercritical CO2 is the primary outcome of the current study.